Dynamic Change of Thyroid Hormones With Postmenstrual Age in Very Preterm Infants Born With Gestational Age <32 Weeks: A Multicenter Prospective Cohort Study - Shi, Ranran; Zhang, Ming; Chen, Yao; Han, Meiying; Xu, Ping; Li, Min; Ding, Yanjie; Zhang, Xiaohui; Kou, Yan; Xu, Haiyan; Zong, Fangru; Liu, Xinjian; et al. (Frontiers in Endocrinology, 2021)
Background: At present, the relationship between thyrotropin (TSH) and free thyroxine (FT4) in relation to postmenstrual age (PMA) in preterm infants is still unclear, and there are no reliable standard thyroid hormone reference ranges, resulting in different diagnostic criteria for congenital hypothyroidism been used by different newborn screening programs and different countries. Objectives: To investigate the relationship between TSH/FT4 and PMA in very preterm infants (VPIs) born with gestational age (GA) <32 weeks and to derive thyroid function reference charts based on PMA. Methods: A prospective observational cohort study was performed on VPIs born with GA<32 weeks and born in or transferred to the 27 neonatal intensive care units from January 1, 2019 to December 31, 2019. Serial TSH and FT4 values were measured at the end of each week during the first month after birth and also at PMA36 weeks, PMA40 weeks and at discharge, respectively. The 2.5th, 5th, 50th, 95th and 97.5th percentiles of TSH and FT4 of different PMA groups were calculated to draw the percentile charts based on PMA. Results: 1093 preterm infants were included in this study. The percentile charts of TSH and FT4 levels based on PMA were drawn respectively, and the result indicated that the percentile charts of TSH values were gradually increased initially and then decreased with increasing PMA. The 97.5th percentile chart reached the peak at PMA30 weeks (17.38μIU/ml), and then decreased gradually, reaching the same level as full-term infants (9.07μIU/ml) at PMA38-40 weeks. The 2.5th percentile chart of FT4 was at its lowest point at PMA26-27 weeks (5.23pmol/L), then increased slowly with PMA and reached the same level as full-term infants at PMA38-40 weeks (10.87pmol/L). At PMA36 weeks, the reference intervals of the 2.5th to 97.5th percentiles of TSH and FT4 were 1.18-12.3μIU/ml and 8.59-25.98pmol/L, respectively. Conclusion: The percentile charts of TSH and FT4 in VPIs showed characteristic change with PMA. The results prompt that age-related cutoffs, instead of a single reference range, might be more useful to explain the thyroid function of VPIs. And repeated screening is necessary for preterm infants.